Color management and control based on image color data - Sameer Syed Mohideen (2014)
Printing of color images on office-use printers has not met the expectation of the user. The printed image can be quite different from the image viewed or captured on the monitor, and thus a major shortcoming of desktop printing/publishing. The cause of such discrepancies in the printed image has been traced to the fact that imaging devices work on the additive property of colors, i.e. red, green, and blue (RGB) forming the gamut of colors, whereas printing devices work on subtractive property of color, i.e. cyan, magenta, yellow and black (CMYK) forming the gamut of colors. A color in one color system is not directly correlated to a color in the other systems, i.e. the color spaces are nonoverlapping, and thus, “What you see is NOT what you get”. This project seeks to find a low cost solution for reproducing color images by investigating the possibility of adding a color control module into Microsoft Print Architecture with a common, customizable interface to the printer driver subsystem, such that image color data can be manipulated to achieve better rendering of the image while printing.